PALBOCICLIB IN COMBINATION WITH HORMONE THERAPY FOR LUMINAL HER2-NEGATIVE METASTATIC BREAST CANCER: NEW HIGHLY EFFECTIVE STRATEGY OF DRUG TREATMENT - E. V. Artamonova (ABV-press, 2017)
The review considers a new oral targeted drug palbociclib and its place in treatment of luminal (estrogen receptor-positive) HER2- metastatic breast cancer. The results of randomized clinical trials have shown that inclusion of palbociclib in various hormone therapy regimens for treatment of HER2- metastatic breast cancer with expression of estrogen receptors allows to significantly improve clinical outcomes and increase survival, objective response rate and its duration, as well as clinical benefit rate (CBR). Addition of palbociclib to letrozole in the 1st line hormone therapy or to fulvestrant in patients with progression at/after previous endocrine therapy increased progression-free survival in all groups irrespective of clinical characteristics, tumor progression, or expression of molecular markers mediating development of hormone resistance. The main adverse events associated with palbociclib were neutropenia, leukopenia and thrombocytopenia, but overall hematological toxicity was manageable, and the therapy itself was safe. This strategy received a "breakthrough therapy designation" from the experts and combines proven effectiveness and satisfactory tolerability, allows to maintain high quality of life, and should be prescribed to patients with luminal HER2- metastatic breast cancer.